Giant filiform polyposis with high-grade dysplasia: A case report and review of the literature. (October 2022) - Kasuga, So; Anzai, Hiroyuki; Makise, Naohiro; Sonoda, Hirofumi; Nagai, Yuzo; Abe, Shinya; Yokoyama, Yuichiro; Ozawa, Tsuyoshi; Emoto, Shigenobu; Murono, Koji; Sasaki, Kazuhito; Kawai, Kazushige; et al.
Abstract: Introduction and importance: Filiform polyposis, a rare condition also referred to as inflammatory polyposis or pseudopolyposis, is commonly observed in cases of inflammatory bowel disease, such as ulcerative colitis or Crohn's disease. It is generally considered a benign tumour characterised by multiple finger-like projections that are mostly observed in the transverse and descending colon. Case presentation: A 69-year-old woman with a history of ulcerative colitis for 18 years who underwent temporary decompression ileostomy for large bowel obstruction at another hospital was referred to our institution for further investigation. Abdominal computed tomography revealed bowel wall thickening of the transverse colon, and colonoscopy revealed stenosis in the hepatic flexure obstructing the endoscope. Although several biopsies of the tumour showed no malignancy, laparoscopic subtotal colectomy with lymph node dissection was performed. Histopathological findings revealed localised filiform polyposis with dysplasia. Clinical discussion: Filiform polyposis has been considered a benign inflammatory polyp without any risk of dysplasia. We accumulated previous cases of giant filiform polyposis and reviewed their characteristics. The presented case of filiform polyposis with ulcerative colitis complicated with high-grade dysplasia highlights the importance of considering malignancy in patients with filiform polyposis. Conclusion: In cases of giant filiform polyposis, even when no malignancy is detected, surgical resection should be considered for the possibility of a malignant component of dysplasia. Highlights: This article is a case report and review of literature for filiform polyposis. Although filiform polyposis is generally considered a benign tumour, present case had dysplasia. This finding highlights the importance of considering malignancy in patients with filiform polyposis.